Dominant and recessive congenital myasthenic syndromes caused by SYT2 mutations. Issue 2 (12th June 2021) - Maselli, Ricardo A.; Wei, David T.; Hodgson, Trent S.; Sampson, Jacinda B.; Vazquez, Jessica; Smith, Heather L.; Pytel, Peter; Ferns, Michael
Abstract: Introduction/Aims: We studied a patient with a congenital myasthenic syndrome (CMS) caused by a dominant mutation in the synaptotagmin 2 gene (SYT2) and compared the clinical features of this patient with those of a previously described patient with a recessive mutation in the same gene. Methods: We performed electrodiagnostic (EDX) studies, genetic studies, muscle biopsy, microelectrode recordings and electron microscopy (EM). Results: Both patients presented with muscle weakness and bulbar deficits, which were worse in the recessive form. EDX studies showed presynaptic failure, which was more prominent in the recessive form. Microelectrode studies in the dominant form showed a marked reduction of the quantal content, which increased linearly with higher frequencies of nerve stimulation. The MEPP frequencies were normal at rest but increased markedly with higher frequencies of nerve stimulation. The EM demonstrated overdeveloped postsynaptic folding, and abundant endosomes, multivesicular bodies and degenerative lamellar bodies inside small nerve terminals. Discussion: The recessive form of CMS caused by a SYT2 mutation showed far more severe clinical manifestations than the dominant form. The pathogenesis of the dominant form likely involves a dominant‐negative effect due to disruption of the dual function of synaptotagmin as a Ca 2+ ‐sensor and modulator of synaptic vesicle exocytosis. Abstract : A. Pes cavus in a patient with a heterozygous mutation in the CB2 domain of synaptotagmin 2 (SYT2). B. Schematic view of SYT2 showing the identified mutation. C. Repetitive stimulation demonstrating presynaptic failure of neuromuscular transmission. D. Distorted neuromuscular junction showing intermingled extensions of the nerve terminal (black asterisks) and Schwann cell (white asterisks), endosomes (white arrowheads), coated pits (black arrows), and a lamellar body (LB). Markers are: 5 mV and 5 ms in C, and 0.6 μm in D.